Effect of CaCO3 addition on ash sintering behaviour during K2CO3 catalysed steam gasification of a Chinese lignite. (25th January 2017) - Zhang, Jiguang; Li, Jianbo; Mao, Yandong; Bi, Jicheng; Zhu, Mingming; Zhang, Zhezi; Zhang, Li; Zhang, Dongke
Highlights: K2 CO3 decreased ash sintering temperature and enhanced ash melting in gasification. CaCO3 addition enhanced ash melting and lowered ash sintering temperatures. CaCO3 reacted with SiO2 to form fluxing phases and amorphous materials. CaCO3 addition inhibited the potassium aluminium silicate formation. CaCO3 addition preserved the catalytic activity of potassium. Abstract: The ash sintering behaviour of a Chinese lignite (LLI) with different amounts of CaCO3 addition during K2 CO3 -catalysed gasification was investigated. 0–10 wt% K2 CO3 was doped into the lignite for catalytic gasification, and CaCO3 was added into the K2 CO3 -doped samples, varying in the range of 0–20 wt% relative to the lignite, for understanding its impact on ash sintering and catalytic gasification activity. Ash samples were prepared by completely gasifying the lignite samples with steam in a fixed-bed catalytic gasification system operating at 1073 K and atmospheric pressure. Sintering temperature, mineralogy and morphology of the ash samples thus obtained were determined using a pressure-drop sintering device, XRD and SEM-EDS, respectively. The results showed that the ash sintering temperature decreased as the K2 CO3 addition increased, indicating that K2 CO3 as the catalyst for gasification would promote ash sintering. SEM imaging analysis showed that all the ash samples from LLI with K2 CO3 addition were composed of agglomerated particles with smooth surfaces, indicating the ashes had incurred partial melting. The degree of melting became more apparent as the K2 CO3 addition ratio increased. These molten phases were identified as K-bearing arcanite and kaliophilite, which contributed to the formation of liquid phases at lower temperatures, resulting in lowered ash sintering temperatures. It was also revealed that the addition of CaCO3 decreased the sintering temperatures of ash samples, indicating that the ash sintering was further enhanced by CaCO3 addition. The surface texture of the ash particles, with the same K2 CO3 addition level, changed from slightly melting to seriously melting or fusion as the CaCO3 addition ratio increased. This is because the addition of CaCO3 suppressed the formation of refractory silicon oxide and generated more fluxing feldspars and lime as well as the amorphous phases. However, the addition of CaCO3 inhibited the formation of water-insoluble kaliophilite and thus helped preserve the catalytic activity of K2 CO3, promoting K2 CO3 catalysed gasification.